What Aspects of Formality Do Workers Value? Evidence from a Choice Experiment in Bangladesh - Minhaj Mahmud; Italo A. Gutierrez; Krishna B. Kumar; Shanthi Nataraj (Institute of Labor Economics (IZA), 2019)
Using a choice experiment among 2,000 workers in Bangladesh, we to elicit willingness to pay (WTP) for specific job benefits typically associated with formal employment. We find that workers value job stability the most; the average worker would be willing to forego a 27 percent increase in monthly income in order to obtain a 1-year written contract (relative to no contract), or to forego a 12 percent increase to obtain thirty days of termination notice. On average, government workers place a higher value on contracts than do private sector employees, while casual workers particularly value higher pay. Our use of choice experiments to overcome the challenges associated with estimating WTP for specific job benefits from hedonic wage regressions or from observed job transitions is of interest in its own right, especially in a developing country context where data on worker transitions are unavailable and many workers are informally employed.
Keywords: J46; J32; J81; 330; informality; worker benefits; discrete choice experiments